The effect of wine closures on volatile sulfur and other compounds during post‐bottle ageing1. (24th January 2013) - He, Juan; Zhou, Qin; Peck, Jim; Soles, Rollin; Qian, Michael C.
ABSTRACT The effect of wine closures on volatile composition during post‐bottle ageing was investigated for Pinot Noir and Chardonnay wines. Natural cork, synthetic cork and screw caps with Saran–tin, Saranex and low density polyethylene (LDPE) liners were investigated over 3 years of storage. Dissolved O2 and SO2 as well as colour were monitored. Volatile sulfur compounds, esters, terpene alcohols, and C13‐norisoprenoids were quantified every 6 months over 3 years. The results showed that the LDPE screw cap gave the highest dissolved oxygen, lowest free SO2 and total SO2 in both wines, while the Saran–tin screw cap gave the lowest dissolved oxygen and the highest free SO2 and total SO2. A decrease of H2S, methanethiol, and thioacetates were observed during the 3 year ageing process for both wines, and their concentrations decreased most in wines sealed with LDPE screw caps and synthetic closures. The decrease of thioacetates was independent of closure type. The accumulation of dimethyl disulfide during storage was not obvious in these two wines. For both wines, no elevated sulfur compounds under any closure were detected; neither dimethyl disulfide nor dimethyl trisulfide were found in any of the experimental wines. Other volatiles also changed with in bottle ageing. Ethyl esters decreased during ageing, whereas ethyl 2‐methylbutanoate and ethyl 3‐methylbutanoate increased during ageing. Terpene alcohols showed a decreasing trend with ageing, as was β‐damascenone, but β‐ionone remained unchanged in Pinot Noir wine during ageing. Both wines under LDPE closure had the highest acetaldehyde at 36 months of ageing. Wine closure affected the concentration of terpene alcohols and C13‐norisoprenoids. Closure had no impact on nerolidol and citronellol, but LDPE screw‐capped wine had lower concentrations of linalool at 36 months of storage. Both wines with LPDE screw cap closures had higher β‐damascenone. Closure had no effect on β‐ionone and other compounds. Copyright © 2013 John Wiley & Sons, Ltd.